Pelaksanaan Perjanjian Penggunaan Tempat Usaha Culinary (Studi Di Food Court "Cetera" Bandara Soekarno Hatta Tangerang Dengan Tenants) - Wahyani, Dyah Arum Kusumo; , Septarina Budiwati, S.H. M.H (2016)
The rapid economic development today raises many business sectors that stand with various field, especially in sector of business. Once of business that's easy to find is the culinary business (food). The development of the culinary business now not only on areas such as food stand or roadside. but also can be found easily in other places, one of which is Food Court that can be found in shopping centre. Not only in Shopping Center, Foud Court also can be found in other places, such as at the airport. One of the airports that provides Food Court is Soekarno Hatta International Airport Tangerang, named is Food Cetera. Businesses that become the object of research is once of the tenants who occupy the Food Court, namely at food stand Bebek Ireng Cak Baz. This research examines and discusses the form of agreement used by the Food Cetera with the tenants. This research method is conduct by empirical juridical approach is a descriptive analysis.